Assessment of Convergence Angle of Tooth Preparations for Complete Crowns Among Dental Students: Typodont vs Simulator - Meriem Amine; Hafsa Oumayma Wahid; Saliha Fahi; Safaa Lehmouddi; Mouna Hamza; Samira Elarabi (International Journal of Dentistry)
Introduction. The technology-enhanced learning and simulation-based learning are critically important pedagogic tools. They allow students to perfect their preclinical training by improving their skills and their manual dexterity while facilitating the acquisition of the know-how necessary for reproduction more realistically and faithfully of the behaviors required for a better dental practice. Retention is one of the mechanical fundamental principles of preparation of cemented fixed prostheses. It depends on several factors including the convergence of the axial walls. The undercut must be sparing in the reduction of tissue volume to obtain a low degree of convergence and a sufficient height of the preparation to comply with the retention and stabilization requirements of the prosthetic element. A draft value of 6° was recommended initially, but a range extending up to 16° has been accepted according to Weed et al. and Dodge et al., as being clinically achievable while providing good retention. Are students able to reproduce, in preclinical, total occlusal convergence (TOC) angles recommended on typodont and simulator? Objective. The evaluation of the TOC of the preparations made on typodont and simulator by the students in the 3rd year of the Faculty of Dental Medicine of Casablanca (FDMC). Material and Methods. A total of 140 dental preparations for cast crowns and metal-ceramics made by thirty-five 3rd year FDMC students were scanned by using the IDENTICA HYBRID optical scanner. The STL files were read by the 3D-TOOL-FREE software, two images were extracted for each preparation using the screen capture tool, and the two mediodistal (MD) and buccolingual angles (BL) were measured by the MB-RULER software. The statistical data were analyzed using the SPSS, software and comparisons were made by Student’s t-test. Results. An overall average of 11.99° ± 4.48 was recorded for the preparations on the typodont with 11.40° ± 5.09 in the MD direction and 12.58° ± 4.74 in the BL direction. Concerning the simulator preparations, we recorded an overall average of 11.31° ± 4.16 with 10.81° ± 4.29 in the MD direction and 11.80° ± 5.44 in the BL direction. No significant difference was observed when comparing the preparations made on the typodont and the simulator. A percentage of 68.6% and 74.3% of the preparations made on the typodont and the simulators respectively fall within an acceptable range of 6 to 16°. Discussion. The TOC values achieved by the majority of students correspond to the recommended values which are 6 to 16° on average. The results of the simulator preparations are similar to the results of Marghalani for dental students at King Abdulaziz University, and Tiu et al., at the University of Otago in New Zealand. Conclusion. This study highlighted the difference between what is taught in dental schools, which is theoretically possible, and the academic results of actual practice. The generally recommended 6° tapers have proven difficult to achieve for many dental students. A margin of 6° to 16° of TOC angle is clinically achievable and allows sufficient retention. We can retain that most of the sample of our study had values that fall within the recommended range.